RATTAN SPECIES AT THREE MOUNTS IN GUNUNG HALIMUN NATIONAL PARK, WEST JAVA - Titi Kalima (Indonesian Journal of Forestry Research, 2004)
Management  of  forest is believed   that many basic knowledges  about  the nature of  the forest is needed.   One of  them is to develop  the forest  as a resource  of  cane industry  in a sustainable way. For this  purpose,  the composition,   distribution  and density  of  rattan  species  in Gunung Halimun National  Park (INGH)   were studied as a model. Data were collected  from December 1994  until May 1995.   For species  composition   on rattan  in TNGH,   three  areas were observed namely in Mt. Kancana,  Mt. Pameungpeuk  and Mt. Pangkulahan  using a continues  belt transect method,   from  the  elevation  of  800-1,400   m above  sea level.  It was  found  that  there  were 13 species of  rattans  in the region.  In terms  of  species   richness  and densities,  Mt. Pameungpeuk comes  first, followed  by Mt. Pangku1ahan  and Mt. Kancana.  Calamus  beteroides, C.javensis,  Daemonorops melanocbaetes, and Plectocomia elongata  are dominant  both in seedling  and nature  forms.  The nature rattans  are relatively abundant   in areas  less  than  1,000 meter  above  sea level and  decrease  in number  of species as well as the minimal population  in the higher altitude.   Calamus  ornatus grows well at 800-1,400 m asl,  while Daemonorops ruber at 800-1,500 m asl, D.oblonga at 800-1,400 m asl.